Red Eye: Next Steps for Conducting Research in Knowledge, Attitude and Practice in Ophthalmology - Francisco J. Bonilla-Escobar; Hugo H. Ocampo-Dominguez (University Library System, University of Pittsburgh, 2013)
Background: Research in Knowledge, Attitude and Practice (KAP) in health sciences is relevant to health care providers and patients to identify factors to address educational interventions.  Methods: A pilot study based on surveys amongst participants in a medical update conference in Cali, Colombia, was conducted to estimate participants' knowledge on red eye in 2011. Results: The population was composed of medical students and general practitioners, with 72.7% of students being in their final year of their training. The classification of red eye was correct in 47% of respondents and we found errors in the classification of emergency, glaucoma and uveitis.  Conclusion: Further research proposals in KAP are required for the recognition of this medical education indicator.